2016
DOI: 10.1002/hep.28894
|View full text |Cite
|
Sign up to set email alerts
|

CD4+Foxp3+ T cells promote aberrant immunoglobulin G production and maintain CD8+ T‐cell suppression during chronic liver disease

Abstract: Persistent hepatotropic viral infections are a common etiologic agent of chronic liver disease. Unresolved infection can be attributed to non-functional intrahepatic CD8+ T cell responses. In light of dampened CD8+ T cell responses, liver disease often manifests systemically as Ig-related syndromes due to aberrant B cell functions. These two opposing yet co-existing phenomena implicate the potential of altered CD4+ T cell help. Elevated CD4+ Foxp3+ T cells were evident in both human liver disease and a mouse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…However, T regs may have a dual role because they are enriched in fibrotic livers and may protect activated HSCs from natural killer (NK) cell-mediated killing, thus allowing them to achieve their full fibrogenic potential (22,23). During chronic liver injury, T regs induce aberrant B cell responses that may contribute to pathogenesis through the expression of CD40L (24).…”
Section: Introductionmentioning
confidence: 99%
“…However, T regs may have a dual role because they are enriched in fibrotic livers and may protect activated HSCs from natural killer (NK) cell-mediated killing, thus allowing them to achieve their full fibrogenic potential (22,23). During chronic liver injury, T regs induce aberrant B cell responses that may contribute to pathogenesis through the expression of CD40L (24).…”
Section: Introductionmentioning
confidence: 99%
“…Foxp3+ regulatory T (Treg) cells play a pivotal role in maintaining immunological self-tolerance and tissue homeostasis by regulating inappropriate immune responses to self-organs and tissues ( 3 ). Under various pathogenic conditions in humans and animal models, Treg cells are recruited into the liver to regulate tissue inflammation and pathology ( 4 8 ). There is also accumulated evidence that tissue Treg cells actively engage in tissue remodeling and repair in stressed or damaged organs, for example, by secreting amphiregulin, a key molecule for tissue regeneration and repair in various inflammation models, including brain ischemia, muscle injury, and viral pneumonia ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, any renal recovery following hepatic transplantation alone may simply be the outcome of successful engraftment and regained liver function . In addition to physiologic perturbations, the intrahepatic milieu fundamentally changes in such a way that implicates aberrant immune responses such as constitutive antibody production . Accordingly, ESLD‐related increases in serum antibody content and immune complexes can potentially accumulate and cause kidney damage .…”
Section: Extrahepatic Manifestations Of Liver Injury and Influence Onmentioning
confidence: 99%
“…1). (38) In addition, during liver injury, activated hepatocytes produce complement proteins, which are key mediators of liver repair. (39)(40)(41) Consequently, studies in human peripheral blood mononuclear cells have found that stimulation through CD46, the complement receptor, in the presence of professional APCs (ie, monocytes and DCs) and inflammatory cytokines can also induce Foxp3 expression on CD4 1 T cells.…”
Section: Extrahepatic Manifestations Of Liver Injury and Influence Onmentioning
confidence: 99%
See 1 more Smart Citation